The plight of the thrift institutions - Carron, Andrew S. (Washington, D.C. : Brookings Institution, 1982)
The book examines the various policy alternatives and identities those that can effectively and efficiently aid the thrifts. Part of any such policy, however, will be a major consolidation of the industry. The author finds that one-fourth of the savings and loan associations must merge to survive, and that substantial government financial assistance will be required to complete the process.
Includes index.
Includes bibliographical footnotes
usc 21/09/2017
Loans
Keywords: Thrift institutions; Financial institutions; United States